The Predictive Validity of IELTS Amongst a Group of MA Syrian Students - Daher, Shadi (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
This study is an attempt to evaluate the predictive validity of the IELTS English language proficiency test from a student’s perspective. It seeks to shed light on the value of this test as an indicator of the academic skills required for overseas students to function in a Western academic context. A group of Syrian MA students studying in British universities were involved in the study.Questionnaires and interviews were the primary research methods used to conduct this research. The results indicate that MA Syrian students involved in the study perceive their IELTS score- and this test in general- as a generally poor predictor for both their academic performance and the problems that they have in connection with the study skills felt necessary for academia. Furthermore, in terms of the difficulties regarding study skills, the students emphasise the need for these skills to be at an advanced level and to extend to critical reading and writing تحاول هذه الدراسة تقييم القيمة التنبؤية لامتحان المقدرة اللغوية IELTS من وجهة نظر الطالب حيث تسعى لإلقاء الضوء على قيمة هذا الامتحان كمؤشر للمهارات الأكاديمية التي يحتاجها الطلاب الأجانب ليعملوا في بيئة أكاديمية غربية. يركز البحث على مجموعة من طلبة الماجستير السوريين في جامعات بريطانية. استخدمت الاستبيانات و المقابلات كطرائق للبحث. تشير النتائج إلى أن الطلاب السوريين المشمولين في الدراسة يرون هذا الامتحان عامة أنه ذو دلالة منخفضة في إمكانيته التنبؤ بأدائهم الأكاديمي و مشاكلهم المتعلقة بالمهارات الدراسية المطلوبة أكاديميا، كمايؤكد هؤلاء الطلاب على الحاجة لتكون هذه المهارات بمستوى أعلى و لتشمل بشكل رئيسي القراءة و الكتابة الناقدة.